2004
DOI: 10.1088/0031-9155/49/5/014
|View full text |Cite
|
Sign up to set email alerts
|

Time–frequency analysis of laser Doppler flowmetry signals recorded in response to a progressive pressure applied locally on anaesthetized healthy rats

Abstract: The laser Doppler flowmetry technique has recently been used to report a significant transient increase of the cutaneous blood flow signal, in response to a local non-noxious pressure applied progressively on the skin of both healthy humans and rats. This phenomenon is not entirely understood yet. In the present work, a time-frequency analysis is applied to signals recorded on anaesthetized healthy rats, at rest and during a cutaneous pressure-induced vasodilation (PIV). The comparison, at rest and during PIV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 28 publications
(39 reference statements)
4
57
0
3
Order By: Relevance
“…The oscillation in interval I and II was considered to reflect the influence of endothelial and endothelial-related metabolic activity (Stefanovska et al 1999;Kvandal et al 2006). The most important role of metabolic regulation is to adjust the blood flow to satisfy the need of cells for oxygen (Humeau et al 2004). The decrease in the muscle oxygenation oscillation here was associated with a decrease in [tHb] to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The oscillation in interval I and II was considered to reflect the influence of endothelial and endothelial-related metabolic activity (Stefanovska et al 1999;Kvandal et al 2006). The most important role of metabolic regulation is to adjust the blood flow to satisfy the need of cells for oxygen (Humeau et al 2004). The decrease in the muscle oxygenation oscillation here was associated with a decrease in [tHb] to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The differences are statistically significant for all the relative activities in the interval 0-200 s following the beginning of the pressure. 16 Moreover, a scalogram study carried out on healthy and type 1 diabetic subjects showed that the neurogenic and endothelial-related metabolic activities are significantly higher during the progressive pressure than at rest, for both healthy and diabetic subjects. However, the relative contribution of the endothelial-related metabolic activity is significantly higher during the progressive pressure than at rest, in the interval 200-400 s following the beginning of the pressure application, but only for healthy subjects.…”
Section: Piv Signalsmentioning
confidence: 99%
“…14 A time-frequency analysis based on wavelets showed that in anesthetized healthy rats there is an increased contribution to PIV response from the endothelial-related metabolic activity, lasting until 400 s after the beginning of the progressive pressure application. 16 The other subsystems (heart, respiration, myogenic, and neurogenic activities) contribute relatively less during PIV than at rest. The differences are statistically significant for all the relative activities in the interval 0-200 s following the beginning of the pressure.…”
Section: Piv Signalsmentioning
confidence: 99%
“…Time and spatial invariance means that, for each characteristic frequency band of the signal, no statistical difference is found for the energy between the two different time intervals, nor between the site analyzed. 2,3,[9][10][11] To study time and spatial variations, it is therefore necessary to analyze the spectrum of impedance signals. However, impedance signals are weakly stationary, i.e., the characteristic frequencies of the signals slightly change continuously.…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…The scalogram has been chosen for this study because it has already proven to be very efficient for physiological signals. 9,10 In order to apply the wavelet transform on the impedance signal, it is necessary to choose a mother wavelet W(t), which will allow a wavelet family to be built by dilatation and translation. This wavelet family is an orthogonal base of the impedance signal.…”
Section: Time-frequency Analysismentioning
confidence: 99%